Long‐term follow‐up of 123 patients with adenocarcinoma of the sinonasal tract treated with endoscopic resection and postoperative radiation therapy. Issue 2 (26th May 2015) - Camp, Sophie; Van Gerven, Laura; Poorten, Vincent Vander; Nuyts, Sandra; Hermans, Robert; Hauben, Esther; Jorissen, Mark
Abstract: Background: Most series about endoscopic resection of adenocarcinomas of the sinonasal tract present outcome data from a small heterogeneous group of patients with a relatively short follow‐up period and a wide variety of histological subtypes and treatment protocols. This relatively large study with a very homogeneous study population updates our experience with a stable treatment protocol looking at survival rates, surgical technique, and prognostic factors. Methods: We conducted a retrospective analysis of the medical records of 123 patients with adenocarcinoma of the intestinal type primarily treated with endoscopic resection and postoperative radiotherapy (RT) in a single tertiary referral center during the period 1992 to 2010. Results: Mean follow‐up was 66 months and median follow‐up was 54 months. Mean and median follow‐up of the subgroup of patients alive at the end of follow‐up was 74 months and 61 months, respectively. At 5‐years of follow‐up, overall survival (OS), disease‐specific survival (DSS), and recurrence‐free survival (RFS) were 68%, 82%, and 62% respectively. At 10‐year follow‐up, these numbers were 51%, 74%, and 45%, respectively. Prognostic factors for treatment outcome are predominantly local recurrence, development of distant metastasis, T classification, histopathological classification, and the center where the first surgery was performed. Conclusion: This large study of sinonasal adenocarcinoma primarily treated with endoscopic resection and RT confirms that this approach results in good oncologic and functional outcome. © 2015 Wiley Periodicals, Inc. Head Neck 38: 294–300, 2016